Keefektifan Penggunaan Virtual Lab Terhadap Penguasaan Konsep Materi Fisika Modern - Isra, Hutri Handayani; Rahman, Mardia Hi (EDUKASI, 2023)
The effectiveness of the Physics learning process, especially in higher education, will be good if the implementation is able to emphasize the process, because the quality of the process will determine learning outcomes. Practicum is very important in order to support learning and emphasize the process aspect. This is based on the aim of learning as a process, namely improving thinking skills, the teaching and learning process using a virtual laboratory can stimulate students to be more active in participating in teaching and learning activities. The class atmosphere became more lively and students were more enthusiastic in participating in the learning process. The purpose of this study was to see student perceptions of the use of virtual laboratories for modern physics topics.